E-137 Endovascular therapy delay for acute large vessel occlusion is associated with worse functional outcome and increased mortality. (23rd July 2022) - Carrion-Penagos, J; Morsi, R; Thind, S; Coleman, E; Brorson, J; McKoy, C; Mendelson, S; Prabhakaran, S; Mansour, A; Kass-Hout, T
Abstract : Introduction: The importance of early mechanical thrombectomy (MT) has shown to improve functional outcomes for patients with acute large vessel occlusion (LVO). As well, prior studies have shown that earlier MT resulted in reduced hospital stay, more home-time, and more desirable living situation in the 90 days after stroke. Hypothesis: We hypothesized that delay in MT in patients with LVO would result in worse clinical outcome and increased mortality. Methods: We performed a retrospective analysis of consecutive patients who underwent MT for LVO in a large academic comprehensive stroke center between 01/2018 and 05/2021. We compared outcomes including in-hospital mortality and 90-day modified Rankin Scale (mRS) based on time from door-to-puncture and door-to-reperfusion, adjusting for relevant covariates using logistic regression. Results: Patients that had shorter door-to-puncture time were found to have higher probability of a lower modified Rankin Scale (mRS 0–2) at discharge (p=0.03). Patients with door-to-puncture less than 60 minutes had a probability of 50% of achieving a good outcome. Longer door-to-puncture times were associated with lower probability of achieving mRS 0–2 at discharge. A similar finding was seen in patients that had shorter times to reperfusion (p=0.05). Adjusting for age, baseline NIHSS score, and final TICI score, delayed door-to-reperfusion time in minutes was an independent predictor of increased mortality at 90 days of 9% for every 10 minutes delay (OR 1.009, 95% CI 1.003–1.016, p=0.006). Every 10 minutes delay in door-to-reperfusion time had 7% higher chance of poor functional outcome at 90 days (OR 1.007, 95% CI 1.004–1.019, p=0.015). Conclusion: Shorter times to MT and reperfusion impact functional outcome and mortality in LVO stroke patients. This indicates that an adequate hospital protocol and continuous education may lead to faster and more efficient stroke activations leading to a shorter time to MT and eventual reperfusion. Goals of door-to-puncture must be established in order to achieve better outcomes. Disclosures: J. Carrion-Penagos: None. R. Morsi: None. S. Thind: None. E. Coleman: None. J. Brorson: None. C. McKoy: None. S. Mendelson: None. S. Prabhakaran: None. A. Mansour: None. T. Kass-Hout: None.